2021
DOI: 10.1080/27658511.2021.1889084
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of native rhizobia nodulating cowpea in major production areas of Ethiopia as influenced by cropping history and soil properties

Abstract: Enumeration of the native rhizobia population is important to determine the abundance of rhizobia in the soil and the achievement of inoculation. In Ethiopia, limited information is available on the population abundance of cowpea nodulating rhizobia. This study aimed to evaluate the population abundance of rhizobia nodulating cowpea and their relation with cropping history and soil properties in cowpea producing areas of Ethiopia. The abundance of rhizobia existing in the soils was assessed by the most probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…The N de ciency could be attributed to low SOM which might have result from low input of plant residues in to the soil. This nding is in agreement with the work ofKebede et al (2021) who observed a strong correlation between SOM and soil N content. Following contamination and subsequent plant growth, N and P contents in the rhizosphere soil increased beyond its critical limits especially during the 12 week period Okalebo et al (2002).…”
supporting
confidence: 93%
“…The N de ciency could be attributed to low SOM which might have result from low input of plant residues in to the soil. This nding is in agreement with the work ofKebede et al (2021) who observed a strong correlation between SOM and soil N content. Following contamination and subsequent plant growth, N and P contents in the rhizosphere soil increased beyond its critical limits especially during the 12 week period Okalebo et al (2002).…”
supporting
confidence: 93%